Implementation of The Merdeka Curriculum in Physics Learning at Senior High Schools in Bengkulu City - Rafikah Dalilah; Andik Purwanto; Iwan Setiawan (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in physics learning at high schools in Bengkulu City, focusing specifically on SMA Negeri 4, SMA Negeri 8, and SMA Negeri 9 Bengkulu City. Additionally, it examines students' responses to implementing the Merdeka Curriculum in physics learning at these three schools. The background of this research stems from the "Merdeka Belajar" (Freedom to Learn) policy introduced by the Ministry of Education and Culture, designed to provide teachers with the flexibility to develop teaching methods that meet students' needs and emphasize assessments measuring fundamental competencies. The Merdeka Curriculum is a response to the evolving challenges in education, aimed at improving the quality of learning through a more flexible, relevant, and student-centered system. This study employs a qualitative method with a descriptive approach. The instruments include module assessment tools, teaching implementation evaluation tools, and student response questionnaires. The findings reveal that implementing the Merdeka Curriculum in physics learning at high schools in Bengkulu City is considered adequate and well-received by students. Students responded positively to various aspects, such as the relevance of the material to real-world issues, the enhancement of critical thinking and collaborative skills, the integration of technology, and the diversity of assessment methods. These positive responses demonstrate that the Merdeka Curriculum successfully fosters a more interactive and meaningful learning experience for students.